Analisis Penggunaan QRIS untuk Optimalisasi Pendapatan UMKM Desa Sirna Baya Kabupaten Karawang - Suherman, Ujang; Ery Rosmawati; Rengga Pratama (Teewan Journal Solutions, 2026)
The development of Micro, Small, and Medium Enterprises (MSMEs) in Karawang Regency is a priority for the Karawang Regency Government. The empowerment of MSMEs is being pursued through the Cooperatives Office, employing various empowerment strategies. For example, in Sirnabaya Village, a village in Teluk Jambe District, Karawang Regency, with a very high population density and a large influx of migrants due to its strategic location close to industrial areas and the city center, it is a potential area for MSME growth and development. However, MSMEs in the area still lack knowledge and use of QRIS as a payment method, even though cashless payment methods are currently trending and popular. To optimize MSME profits in line with technological developments, a research project entitled